THE IMPLEMENTATION OF ADA SCREENING TOOLS TO DETERMINE THE BLOOD SUGAR TEST FLOW IN POSYANDU LANSIA - Winarismasari, Khoirunnisa Yunita; Candra Bumi (Universitas Airlangga, 2024)
Abstract Introduction: The high incidence of undiagnosed diabetes may increase the incidence of T2DM. Therefore, prediabetes screening activities are needed to detect prediabetes cases early to prevent them from developing into T2DM. Methods: A descriptive research analysis with a cross-sectional approach was conducted in Posyandu Lansia in the area of Sumbersari Health Centre, Jember. The population of this study was all people who visited the Sumbersari Health Centre aged 40 years and over. The number of samples obtained as many as 246 with the sampling technique is systematic random sampling. The Data processing was done descriptively and using the ROC (Receiver Operating Characteristic) test to see the results of the diagnostic test of the ADA Diabetes Risk Test instrument at the Sumbersari Health Centre with a random blood sugar test comparison. Results: From a total of 246 subjects, 159 had prediabetes. The sensitivity value at cut point 5 of 66% and specificity of 36% with a PPV value of 38% and NPV of 64%. While at the optimal cut-off point of 4, the sensitivity value is 90%, and the specificity value is 22%, with a PPV value of 40% and NPV of 77%. Moreover, the ROC curve has an AUC value that is statistically considered less effective, with a value of 56%. Conclusion: ADA Diabetes Risk Test shows promising results for prediabetes screening in the Sumbersari population with high sensitivity for determining disease. Keywords: ADA Diabetes Risk Test, Diabetes Mellitus Type 2, Prediabetes,